MAKING SENSE OF THE ANTI-SAME-SEX-MARRIAGE MOVEMENT IN FRANCE. Issue 2 (1st July 2019) - Gunther, Scott
Abstract : This article examines the political style and rhetoric of the Manif pour tous (MPT), the main organization opposing same-sex marriage in France, from summer 2013 to the present. It exposes how the MPT's style and rhetoric differ from those of their American counterparts, and what this tells us about the different strategies of political movements in France and the United States generally. It is based on an analysis of the language used by activists whom I interviewed in 2014 and 2015 and on a discourse analysis of the MPT's website, Facebook page, Twitter feed, and press releases since 2013. This analysis of the distinctive features of the MPT brings to light underlying concerns about French identity in the face of globalization. In other words, for the MPT and its members, what is at stake is not just same-sex marriage but the very definition of Frenchness.